Biodiversity of Penicillium species from marine environments in Portugal and description of Penicillium lusitanum sp. nov., a novel species isolated from sea water. Issue 10 (20th June 2019) - Gonçalves, Micael F. M.; Santos, Liliana; Silva, Bruno M. V.; Abreu, Alberto C.; Vicente, Tânia F. L.; Esteves, Ana C.; Alves, Artur
Abstract : During an extensive survey of marine fungi in coastal marine environments from Portugal, a collection of Penicillium isolates were obtained from sea water, macroalgae and driftwood. Sixteen distinct Penicillium species were identified with Penicillium terrigenum and Penicillium brevicompactum being the most frequent. A Penicillium species isolated from sea water could not be affiliated to any known species. Phylogenetic analyses based on the ITS region of the rDNA and the beta-tubulin ( benA ) gene placed it into Penicillium section Ramosa, distinct from all currently known species and with Penicillium tunisiense as its closest relative. Although having similar morphological characteristics, these species differ in micromorphological and molecular characters. Thus, Penicillium lusitanum sp. nov. is proposed as a novel species.